A Commitment to Experience Must Reach Across the Continuum of Care - Jason Wolf (Patient Experience Journal)
A conversation on patient experience is not restricted to one care setting, nor should it be. People's healthcare journeys are not singular instances, but most often a series of encounters that while perhaps separate operationally from the delivery side of care, all weave together to frame one experience for a patient, their family members and care partners. This special issue purposefully takes us outside the traditional conversation space for experience, looking at segments of the care continuum including primary care, ambulatory care, free clinics and even dental care and the use of non-traditional care methods such as telehealth and app-based technologies to reinforce positive experiences. While this issue explore experience in the non-acute setting, we also offer a call to action on how we continue to ensure the best in experience for all across the continuum of care. In the end, we all know a commitment to experience in healthcare is not isolated to one idea, one organization, or one segment of healthcare. It is an accountability we all share, an opportunity we all must take, and ultimately a promise we all must make to one another and all we serve in healthcare.